2009
DOI: 10.2334/josnusd.51.383
|View full text |Cite
|
Sign up to set email alerts
|

Non-bioabsorbable vs. bioabsorbable membrane: assessment of their clinical efficacy in guided tissue regeneration technique. A systematic review

Abstract: In a 1998 review article, Laurell andcolleagues performed a meta-analysis of relevant guided tissue regeneration (GTR) articles over the previous 20 years (1). The purpose of the present research was to expand on that work, particularly searching for trends discriminating between bioabsorbable and nonbioabsorbable barriers, as well as the use of enamel matrix derivative, with respect to interproximal bony defects. The most recent periodontal journals were reviewed and a search of PubMed (National Institutes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 76 publications
(22 reference statements)
4
48
1
1
Order By: Relevance
“…This finding is in agreement with the conclusions of a recent systematic review (28), which showed that intrabony defects treated with collagen barrier without grafting materials resulted in a mean CAL gain of 2.44 mm, with a range of 2.0 mm to 2.58 mm and collagen barriers with graft material resulted in a mean CAL gain of 3.48 mm, with a range of 2.3 mm to 4.1 mm. Our results are also in good conformity with those of other authors who reported enhanced clinical success when GTR was performed with barrier membranes and bone replacement grafts (4)(5)(6)(7)(8).…”
Section: Discussionsupporting
confidence: 82%
“…This finding is in agreement with the conclusions of a recent systematic review (28), which showed that intrabony defects treated with collagen barrier without grafting materials resulted in a mean CAL gain of 2.44 mm, with a range of 2.0 mm to 2.58 mm and collagen barriers with graft material resulted in a mean CAL gain of 3.48 mm, with a range of 2.3 mm to 4.1 mm. Our results are also in good conformity with those of other authors who reported enhanced clinical success when GTR was performed with barrier membranes and bone replacement grafts (4)(5)(6)(7)(8).…”
Section: Discussionsupporting
confidence: 82%
“…[26][27][28] However, no RCTs were identified that addressed the relationship between regenerative treatment and endodontic treatment.…”
Section: Relationship Of Regenerative Treatment To Endodontic and Ortmentioning
confidence: 96%
“…Eine bewährte Technik zur Vermeidung einer epithelialen Ausheilung nach der Parodontalchirurgie ist der Einsatz von Membranen. Diese lassen sich aufgrund ihrer biologischen Eigenschaften in resorbierbare und nichtresorbierbare Membranen einteilen [66]. Evidenz fĂźr ihren erfolgreichen Einsatz existiert bei der Therapie von Unterkiefermolaren mit Furkationsbefall bis Grad 2, vertikale intraossäre Defekte mit zwei oder drei Wänden und gingivale Rezessionen [24,37,89].…”
Section: Zahnbewegung Bei Parodontalen Defektenunclassified
“…A triedand-tested technique for preventing an epithelial healing following periodontal surgery is membrane application. These membranes are classified as resorbable or non-resorbable according to their biological properties [66]. There is evidence of the successful implementation of membranes for treating mandibular molars with furcation defects up to degree II, vertical two-and three-wall intraosseous defects or gingival recessions [24,37,89].…”
Section: Zahnbewegung Bei Parodontalen Defektenmentioning
confidence: 99%